THE ROLE OF JOB SATISFACTION MEDIATE THE INFLUENCE OF SITUATIONAL LEADERSHIP AND CAREER DEVELOPMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF BLU EMPLOYEES BUSINESS CAPITAL MANAGEMENT INSTITUTIONS MARINE AND FISHERIES (LPMUKP) - Ayu Anggraini, Ditta; Singmin Johanes Lo (Dinasti International Journal of Digital Business Management, 2020)
This study aims to analyze the role of job satisfaction in mediating the influence of situational leadership and career development on organizational citizenship behavior (OCB) of BLU employees of the Marine and Fisheries Business Capital Management Institution (LPMUKP). This research was conducted from September 2019 to March 2020 at BLU LPMUKP. The research method used a quantitative approach, the population in this study were all BLU LPMUKP employees totaling 294 employees consisting of permanent and temporary employees. The sample used in this study were permanent employees of 81 respondents using saturated sampling technique. The data collection techniques using interviews and questionnaire instruments. Data were analyzed using structural equation modeling (SEM) with the Smart PLS 3.2.7 software program. The results of this study indicate that situational leadership and career development have a positive and significant effect on organizational citizenship behavior. Meanwhile, job satisfaction is no more effective in mediating situational leadership and career development on organizational citizenship behavior as without mediation of situational leadership and career development would greatly affect organizational citizenship behavior in BLU LPMUKP.